The Impact of AI-Based Business Analytics on Corporate Strategic Decision Making - Daquan Gosheven; Langundo Philly; Taila Taila (IHSA Institute, 2025)
The rapid growth of digital transformation has encouraged organizations to increasingly adopt AI-Based Business Analytics to enhance strategic decision making in highly dynamic and competitive business environments. Artificial Intelligence (AI) technologies, including machine learning, predictive analytics, and real-time data processing, enable organizations to generate faster, more accurate, and evidence-based insights that support executive decision making and improve organizational performance. This study aims to examine the impact of AI-Based Business Analytics on corporate strategic decision making. A quantitative research approach was employed using an explanatory cross-sectional survey design. Data were collected from 300 corporate executives, strategic planning managers, business analysts, senior managers, and AI implementation specialists working in organizations that have adopted AI-enabled business analytics. The data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) to evaluate the measurement and structural models and test the proposed hypotheses. The findings indicate that AI-Based Business Analytics has a positive and statistically significant influence on corporate strategic decision making. The results also demonstrate that AI-generated insights enable organizations to make more informed and adaptive strategic decisions in increasingly uncertain business environments. The study concludes that adopting AI-Based Business Analytics strengthens organizational strategic decision-making capabilities, enhances sustainable competitive advantage, and supports long-term organizational performance. These findings contribute to the literature on Strategic Management, Artificial Intelligence, Business Analytics, and Decision Science while providing practical guidance for organizations seeking to maximize the strategic value of AI-driven analytics in corporate decision-making processes.